2009
DOI: 10.1038/ja.2009.1
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and biological properties of 4″-O-acyl derivatives of 8a-Aza-8a-homoerythromycin

Abstract: A series of 4 00 -O-acyl derivatives of 8a-aza-8a-homoerythromycins A were synthesized and tested against Gram-positive and Gram-negative bacteria. Derivatives of 8a-aza-8a-homoerythromycin A have potent anti-bacterial activity against not only azithromycin-susceptible strains, but also efflux (M) and inducible macrolide-lincosamide-streptogramin-resistant Gram-positive pathogens. These compounds show moderate to high clearance and low oral bioavailability in preliminary in vivo pharmacokinetic studies in rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…7,8 In the past we have performed chemical modification of macrolides first by varying substituents at 9a-N-position of the azithromycin scaffold, 9 and then by modifying 8a-lactam at C(3)-OH 10 and C(4 00 )-OH positions. 11 Our recent communication reported on synthesis and antibacterial activities of the first macrolide compounds with 4 00 -O-(3-amino)propionyl unit as a part of the linker tethering the second structural unit. 12 This position was lately explored by other groups as well and they have shown that introducing carbamate functionality on position 4 00 of azithromycin lead to improved in vitro antibacterial activity against resistant Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In the past we have performed chemical modification of macrolides first by varying substituents at 9a-N-position of the azithromycin scaffold, 9 and then by modifying 8a-lactam at C(3)-OH 10 and C(4 00 )-OH positions. 11 Our recent communication reported on synthesis and antibacterial activities of the first macrolide compounds with 4 00 -O-(3-amino)propionyl unit as a part of the linker tethering the second structural unit. 12 This position was lately explored by other groups as well and they have shown that introducing carbamate functionality on position 4 00 of azithromycin lead to improved in vitro antibacterial activity against resistant Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Among 14-membered derivatives, cethromycin [10e13], a 3-keto derivative, seems to exhibit antibacterial potency against resistant pathogens comparable/exceeding to telithromycin. In the past decade, we have explored 15-membered macrolide cores, including modifications on the N-9 position of aglycone ring [14e16], 3-decladinosyl derivatives [17,18] and acyl derivatives on 4 00 -position of cladinose [19] without achieving desirable antimicrobial profile.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 In choosing a new hexaketide target, we were motivated by amidecontaining derivatives of erythromycin that show antibiotic activity comparable to azithromycin. [71][72][73][74][75] Thus, the impact of exchanging a central native C-Me functionality to N-H, creating an amide group in the chain-elongation intermediate (Scheme 1B) became a central objective. This choice was also made to assess the impact of a single heteroatom replacement in the chain on TE-mediated cyclization.…”
Section: Chemical Synthesis Of Amide Hexaketide Substratementioning
confidence: 99%